PENERAPAN METODE KOOPERATIF TAI DALAM MENENTUKAN KALIMAT UTAMA PADA PARAGRAF SISWA KELAS IV SD INPRES PABARUNG KECAMATAN TOMBOLO PAO KABUPATEN GOWA - Amir Amir (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2017)
The purpose of this classroom action research is to know the ability of students to determine the main sentence in the paragraph through the application of cooperative methods TAI is expected to improve the process and results of learning Indonesian fourth graders Elementary School Pabarung District Tombolo Pao. The technique used in this research is a qualitative description. The class action research plan is implemented in two cycles. Each cycle has four stages: planning, implementation, observation, and reflection.The results showed that there were 0% of students in very low category, 6.67% of students in randah category, 26.67% in medium category, 50% in high category and 16.67% in very high category. The average score in cycle I was 69.83 in the